Lucretius’ Atomism as an Ideological Forerunner of Modern Astronomy - Helenius, Visa (Pohjois-Suomen Historiallinen Yhdistys ry, 2025)
The modern astronomic picture of the universe is astonishing: outer space is filled with a myriad of planets, stars, galaxies, and black holes, and it seems that the universe has come into existence through a primordial explosion. The modern image has required highly developed scientific devices, such as powerful telescopes. In antiquity, the description of the celestial world was established by ordinary observation of the sky, empirical reasoning and primitive astronomical devices. Titus Lucretius Carus, a poet, philosopher and an adherent of Epicureanism in the late Roman period, favoured experience and empirical reasoning. Although he is not an astronomer and propounds incorrect, obsolete, and unclear astronomical views, I argue in this article that he is an ideological forerunner of modern astronomy. Specifically because (1) his work De rerum natura was a source of inspiration for natural scientist especially in the early modern period, (2) his astronomical views and modern astronomy have points of contact and (3) he discusses matters, which are topical in modern astronomy.